METHANE CONCENTRATIONS IN NATURAL GAS: THE GENETIC IMPLICATIONS - Mango F.D. (My University, 2001)
The current controversy over the origin of non-biogenic gas (i.e. thermal or catalytic) might be resolved if original gas composition were known. For example, if it were about 50% methane, as typically seen in thermal cracking, then there could be little doubt about the conventional view that natural gas is thermal in origin. If, on the other hand, it were closer to 80% methane, a composition seen in produced gas but rarely seen in thermal cracking, a thermal origin would then be in doubt. Unfortunately, original composition is obscured by fractionation during generation and migration. Thus, gas composition in any one deposit (e.g. in source rocks, reservoir rocks, oils, waters, and so on) need not reflect original composition. However, an accurate mass balance of all gas deposits including dispersed and escaped gas could reflect original composition. The mass balance presented here suggests an original composition close to 74% methane, a composition that cannot be explained by thermal cracking alone. It calls for methane enrichment, perhaps through catalytic input or mixing with biogenic gas.